Типологічні особливості особистісної ідентичності засуджених до позбавлення волі жінок - Герасименко, О. А.; Herasymenko , O. A. (Вісник Харківського національного університету імені В. Н. Каразіна. Сер.: Психологія. - 2021. - Вип. 70. - С. 94-102, 2021)
У статті проаналізовані напрацювання науковців, що розглядали ідентичність, як психологічний та соціальний феномен. Особистісну ідентичність розглянуто як важливий ресурс ресоціалізації засуджених. Відзначено яких перемін зазнає особистісна ідентичність за час відбування покарання, що пов’язано зі зміною соціальних ролей і самоставлення, соціальною стигматизацією, порушенням сімейних зв’язків, труднощами при відновленні соціального функціонування (пошуку роботи, житла тощо). Висвітлено важливість проблеми ресоціалізації засуджених, яка зумовлена необхідністю забезпечення індивідуального підходу до засуджених та осіб, які звільнились з місць позбавлення волі, недопущення їх повернення до кримінального способу життя, формування у них соціально сприятивих форм поведінки після звільнення. Емпірично виявлено типологію особистісної ідентичності засуджених до позбавлення волі жінок на етапі їх ресоціалізації. Виявлено змістовні характеристики типологічних особливостей особистісної ідентичності жінок, засуджених до позбавлення волі та їх вплив на процес ресоціалізації засуджених, що може бути використана для розробки заходів їх психологічного супроводу і корекції.

The article analyzes the work of scientists who considered identity as a psychological and social phenomenon. The concept of identity as a complex integrated socio-psychological formation and as a category of adaptive resources of the individual is considered. The problem of formation of personal identity and its influence on socialization and formation of human personality is covered. The insufficiency of theoretical substantiations of studying the peculiarities of personal identity as a structural component of the personality of women sentenced to imprisonment is shown. Personal identity is considered as an important resource for resocialization of convicts. It is noted what changes the personal identity undergoes during the sentence, which is associated with changes in social roles and self-esteem, social stigma, disruption of family ties, difficulties in restoring social functioning (job search, housing, etc.). The importance of the problem of resocialization of convicts, which is due to the need to ensure an individual approach to convicts and persons released from prisons, preventing their return to a criminal lifestyle, the formation of socially favorable forms of behavior after release. The process of resocialization is considered as a complex problem determined by the social environment in which the punishment takes place, the specifics of interpersonal interactions in this environment, the psychological characteristics of the personality of convicts. The study empirically identified the typology of personal identity of women sentenced to imprisonment at the stage of their resocialization, which includes four types of women sentenced to imprisonment: passive-depressed, sociable, self-confident, infantile. The given meaningful description of the types of personal identity of women sentenced to imprisonment can be used to develop measures for their psychological support and correction.

В статье проанализированы наработки ученых, рассматривавших идентичность как психологический и социальный феномен. Личностная идентичность рассмотрена как важный ресурс ресоциализации осужденных. Отмечены какие изменения испытывает личностная идентичность за время отбывания наказания, что связано с изменением социальных ролей и самоотношения, социальной стигматизацией, нарушением семейных связей, трудностями при восстановлении социального функционирования (поиска работы, жилья и т.п.). Освещена важность проблемы ресоциализации осужденных, которая обусловлена ​​необходимостью обеспечение индивидуального подхода к осужденным и освободившимся из мест лишения свободы, недопущение их возвращение к криминальному образу жизни, формирование у них социально благоприятных форм поведения после освобождения.
Typological features of the personal identity of women convicted to deprivation of freedom
Keywords: особистісна ідентичність; засуджені жінки; ресоціалізація; адаптаційні ресурси особистості; типологія ідентичності; психологічне дослідження; соціальне середовище; групи досліджуваних; personal identity; convicted women; resocialization; adaptive resources of the individual; typology of identity; psychological research; social environment; groups of subjects; личностная идентичность; осужденные женщины; ресоциализация; адаптационные ресурсы личности; типология идентичности; психологическое исследование; социальная среда; группы испытуемых